Transforming point cloud data into 3D BIM models: a case study on slabs - Slávek Zbirovský; Václav Nežerka (Acta Polytechnica CTU Proceedings)
We explore the automatized transition of point cloud data into a Building Information Model (BIM), an essential task for reconstructions, demolition plans, or auditing. In this study, we use point cloud data generated by 3D laser scanning. The research elaborates on the process of segregating and segmenting floor slabs from point clouds and the developed algorithms categorize point cloud subsets based on different height parameters (z-coordinates). Once slabs are identified, a function is applied to create envelopes for each slab level, accommodating any convex or concave shape. The resulting geometry, along with relevant auxiliary data, is exported in the Industry Foundation Classes (IFC) format, a standard for BIM data exchange. The exported entities can then be further processed using prevalent software such as Revit or ArchiCAD.